2013
DOI: 10.3164/jcbn.13-18
|View full text |Cite
|
Sign up to set email alerts
|

Changes of energy metabolism, nutritional status and serum cytokine levels in patients with Crohn’s disease after anti-tumor necrosis factor-α therapy

Abstract: We investigated the effects of treatment with antibodies against tumor necrosis factor (TNF)-α on energy metabolism, nutritional status, serum cytokine levels in patients with Crohn’s disease (CD). Twelve patients were enrolled. Resting energy expenditure (REE) levels were measured by indirect calorimetry. Crohn’s disease activity index (CDAI) significantly decreased after treatment with anti-TNF-α therapy. Anti-TNF-α therapy did not affect REE, but respiratory quotient (RQ) significantly increased after treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…Previous studies have reported improvements in nutritional status and metabolism after infliximab therapy but did not measure vitamin D levels per se. 29,30 …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported improvements in nutritional status and metabolism after infliximab therapy but did not measure vitamin D levels per se. 29,30 …”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that anti-TNF-α therapy did not affect mREE but significantly increased the RQ in adult CD patients. ( 16 ) However, the relationship between energy expenditure and disease activity in adult UC patients remains unclear, although we previously reported a significant correlation between mREE and the Lichtiger index. ( 15 )…”
Section: Discussionmentioning
confidence: 93%
“…Recently, we evaluated the changes in the energy metabolism of CD patients receiving anti-tumor necrosis factor (TNF)-α therapy and showed that anti-TNF-α therapy significantly increased the RQ but did not affect the mREE. ( 16 ) These results suggested that the principal metabolic substrate might shift from fat to carbohydrate oxidation after anti-TNF-α therapy. However, there are no reports about metabolic changes due to medical treatment in UC patients.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…20 The selection of a proper therapy, such as biological therapy, which is used with increasing frequency, seems not only to mitigate the inflammatory process in the gastrointestinal (GI) tract, but also to provide beneficial effects on the nutritional status of patients with CD, thus denoting the increasing importance of medications in vitamins and micronutrient levels. 21 Taken together current evidence suggests that vitamins might play an important role for the disease course and outcome of IBD patients. It is of great importance to gain a deeper understanding about vitamin and iron status via regular nutritional monitoring in IBD patients.…”
Section: Introductionmentioning
confidence: 92%